Efficacy of Oxyclozanide and Closantel against Rumen Flukes (Paramphistomidae) in Naturally Infected Sheep - García-Dios, David (Animals (Basel), 2020)
SIMPLE SUMMARY: Paramphistomosis, caused by ruminal trematodes, is currently considered an emergent disease in Europe due to the progressive increase of prevalence and reports of acute cases in ruminants. Thus, finding effective control methods such as efficient drugs against paramphistomids is currently a priority. Although some drugs have been found effective for treating paramphistomid infections in cattle, data in sheep are currently limited. A single administration of oxyclozanide (15 mg/kg) or closantel (10 mg/kg) has been proven efficient in cattle, but it has not been tested in sheep; thus, the aim of the present study was to assess the effectiveness of these treatment protocols against paramphistomids in naturally infected sheep. The treatment with oxyclozanide was very efficient since it significantly reduced the paramphistomid egg output in more than 90% during 11 weeks after treatment. In contrast, closantel showed low efficacies throughout the study. The results of this study support the use of a single oral dose of oxyclozanide at 15 mg/kg for treating paramphistomid infections in sheep, whereas a single oral dose of closantel at 10 mg/kg is not effective. ABSTRACT: Paramphistomosis is considered an emergent disease of ruminants in Europe. Some drugs have been found effective for treating paramphistomid infections in cattle, but data in sheep are currently limited. Thus, faecal samples from 25 adult sheep naturally infected with paramphistomids were collected weekly to test the efficacy of oxyclozanide and closantel. Three groups were performed: nine animals orally treated with a single dose of oxyclozanide (15 mg/kg bodyweight (BW) integrated the G-OXI group, whereas eight sheep orally treated with a single dose of closantel (10 mg/kg BW) were placed in a group called G-CLS. Eight untreated controls constituted the group G-CON. Oxyclozanide showed efficacies up to 90% until week 11 post-treatment, with a maximum efficacy of 98.3%, and significant differences were found between G-OXI and G-CON until the 26th week post-treatment. Closantel was insufficiently active (0–81%) throughout the study and differences compared to G-CON were never found. The present study reveals that oxyclozanide given at a single oral dose of 15 mg/kg BW is highly effective against adult rumen flukes in sheep. In addition, the use of a single oral dose of closantel at 10 mg/kg BW is not recommended for treating paramphistomid infections in sheep.